Multi-faceted and holistic risk management for business-critical food-safety events causing major disruption to both small and large businesses – An illustrative model. (April 2022) - Robertson, Rosalind; Beaven, Anna; Coolbear, Tim; Hill, Jeremy; Kirk, Tim; McCullough, Greg; Piper, Mark; Venter, Pierre
Abstract: In the food industry, a reactive, siloed approach to food safety is common; the proactive application of a broad risk management (multi-faceted risk management) approach is in a relatively early stage of evolution. This paper shows that opportunities exist to move beyond the typical mono-dimensional approaches that focus only on fixing specific causes and look at the broader risks associated with any event. Companies providing nutrition globally face a broad risk landscape across products, geographies, media platforms and Governments, regardless of business size. Multi-faceted risk management has been applied for some time across other industries and provides a useful set of tools to further develop within the food sector. Each event creates a unique series of risks for an affected company. More often than not, these are further enhanced by factors that are external to the company itself. In this paper, the same theoretical food safety event is placed in the context of both a small-scale boutique business and a large-scale corporate business, and a semi-quantitative multi-faceted risk management model is applied to determine and select mitigation options. The illustrative model considers not only the food safety risk, but also various risk facets relevant to the business, population, societal, environment, reputation and public perception. Consideration is also given to additional external events, such as occurrence under the circumstances of a coincidental catastrophic condition. The use of the model in business continuity planning to identify event likelihood and consequences, and therefore pre-emptive identification and emplacement of preventative measures is also illustrated.